Environmental technology and a multiple approach of competitiveness - Milad Abdelnabi Salem; Fekri Ali Mohammed Shawtari; Hafezali Iqbal Hussain; M. F. Shamsudin (Future Business Journal, 2020)
This paper investigates the relationships between environmental technology and competitiveness focusing on 224 industrial corporations. To date, there is still a debate regarding the benefits of being green. Previous literature has investigated this relationship mostly in developed countries. Additionally, the majority of these studies do not disaggregate the environmental practices and competitiveness. Less attention has been given to the environmental issues in developing countries. This study aims to fill these gaps by breaking down the environmental technology into two processes and products-focused practices and investigating their effects on the multiple approaches of competitiveness represented by image-, profits-, and satisfaction-related aspects of competitiveness. The study adopts a crosssectional study using a self-reported questionnaire. The collected data are analysed using structural equation modelling technique based on AMOS methods. The results revealed that only products-focused practices could improve the three dimensions of competitiveness. The processes-focused practices did not contribute to any of the competitiveness aspects. Such results provide new insight for the application of resource-based view theory in green-based developing countries.
Keywords: 650; Environmental technology; Industrial sector; Competitiveness; Structure equation modelling